PEMBERDAYAAN MASYARAKAT MELALUI LEMBAGA SOSIAL DAN PENDIDIKAN - Bayu Adi Laksono; Nasyikhatur Rohmah (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2019)
Abstract : The purpose of this study is to explore the role of social and educational institutions in Bajulmati in the process of community empowerment. This study used a qualitative approach, and was carried out in Bajulmati Hamlet, Gajahrejo Village, Gedangan District, Malang Regency. Informants in this study consisted of government institutions, activists empowering from social and educational institutions, and surrounding communities. Data collection uses interviews, documentation and observations and analyzed by miles and huberman models. The results of the study show the role of social and educational institutions in empowering the Bajulmati community. In the economic field, the community is empowered through the use of natural and human potential. In the social field, it is empowered to always be optimistic and independent. As well as in the field of education, the community is empowered through educational institutions that are built, both schooling and education outside the school system. Schooling education aims to increase competitiveness, education outside the schooling system to maintain the culture and noble values of the Bajulmati community.Abstrak Tujuan dari penelitian ini adalah menggali peran lembaga sosial dan pendidikan di Bajulmati dalam proses pemberdayaan masyarakat. Penelitian ini menggunakan pendekatan kualitatif, dan dilaksanakan di Dusun Bajulmati, Desa Gajahrejo, Kecamatan Gedangan, Kabupaten Malang. Informan dalam penelitian ini terdiri dari institusi pemerintahan, pegiat pemberdayaan dari lembaga sosial dan pendidikan, serta masyarakat sekitar. Pengumpulan data menggunakan wawancara, dokumentasi dan observasi serta dianalisis dengan model miles dan huberman. Hasil penelitian menunjukkan peran lembaga sosial dan pendidikan dalam memberdayakan masyarakat Bajulmati. Dalam bidang ekonomi, masyarakat diberdayakan melalui pemanfaatan potensi alam maupun sumber daya manusia. Dalam bidang sosial, diberdayakan untuk selalu bersikap optimis dan mandiri. Serta dalam bidang pendidikan, masyarakat diberdayakan melalui institusi pendidikan yang dibangun, baik pendidikan persekolahan maupun pendidikan di luar sistem persekolahan. Pendidikan persekolahan bertujuan untuk meningkatkan daya saing, pendidikan di luar sistem persekolahan untuk menjaga budaya dan nilai-nilai luhur masyarakat Bajulmati.